2019
DOI: 10.1093/abbs/gmz129
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of crosstalk between LX-2 and liver cancer stem-like cells from MHCC97H cells by DFOG via inhibiting FOXM1

Abstract: Hepatic stellate cell (HSC) line LX-2 is activated by liver cancer stem-like cells (LCSLCs) and produces various cytokines that make up most of the hepatocellular carcinoma (HCC) microenvironment. The new genistein derivative, 7-difluoromethoxyl-5,4′-di-n-octylgenistein (DFOG), shows anticancer effects in multiple malignancies by controlling forkhead box M1 (FOXM1). In this study, we aimed to assess whether DFOG disrupts the crosstalk between human HSC LX-2 cells and LCSLCs. Distinct generations of MHCC97H-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…with miR-34a downregulation has an important function in liver cancer progression [28]. In addition, we and others have shown that FOXM1 is a key regulator of stemness in various cancers, including liver cancer [29,30]. We found that the 3′-UTR of human FOXM1 mRNA contains a possible miR-34a binding site by TargetScan (Figure 7(a)).…”
Section: Foxm1 Is a Direct Mir-34a Target In Lcscs It Was Demonstratmentioning
confidence: 68%
“…with miR-34a downregulation has an important function in liver cancer progression [28]. In addition, we and others have shown that FOXM1 is a key regulator of stemness in various cancers, including liver cancer [29,30]. We found that the 3′-UTR of human FOXM1 mRNA contains a possible miR-34a binding site by TargetScan (Figure 7(a)).…”
Section: Foxm1 Is a Direct Mir-34a Target In Lcscs It Was Demonstratmentioning
confidence: 68%
“…The investigation of the crosstalk between HSCs and CSCs resulted in the identification of the transcription factor Forkhead Box M1 (FOXM1) as a main player in HSC activation and maintenance of stemness in CSCs in vitro. FOXM1 inhibition in co-cultures of these two populations disrupted the crosstalk, whereas the overexpression of FOXM1 reversed the effects of the inhibition [220]. These lines of research highlight additional potential targets to interrupt the communication between HSCs and cancer (stem) cells, with the ultimate goal of targeting the CSC via multiple approaches.…”
Section: The Csc Niche In Hcc: Ectopic Lymphoid Structures and Hepatimentioning
confidence: 94%
“…FOXM1 ranks among the most diferentially expressed genes. In this study, we focus on FOXM1 because it is involved in cancer stemness and metastasis [27][28][29]. Dysfunction of FOXM1 occurs in several malignant cancers and is highly correlated with poor prognosis and enhanced metastasis [13][14][15].…”
Section: Discussionmentioning
confidence: 99%